ASISTENSI PELAPORAN SPT TAHUNAN PPH BERBASIS CORETAX SEBAGAI UPAYA PENINGKATAN KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Eduard Ary Binsar Naibaho; Antonius Herusetya; Mulyadi Noto Soetardjo; Lina; Renna Magdalena; Irwan Wisanggeni; Pikanti Endah Artati (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
This study examines a community service (PkM) activity carried out by Universitas Pelita Harapan (UPH) in collaboration with KPP Pratama Tiga Raksa under Kanwil DJP Banten, focusing on assisting individual taxpayers in filing their 2025 Annual Personal Income Tax Returns (SPT Tahunan PPh OP) using the CoreTax system implemented by the Directorate General of Taxes (DGT). The CoreTax system represents a transformational shift in Indonesia's tax administration, replacing the previous e-Filing platform with a more integrated and real-time digital infrastructure. The activity was conducted on March 12, 2026 at the Spark Labs FEB, Gedung F UPH, Tangerang. Employing a descriptive participatory approach, the program involved tax volunteer students (Relawan Pajak) supervised by accounting faculty members who provided direct guidance to taxpayers, comprising UPH lecturers, staff, and surrounding community members, in navigating the CoreTax portal. Two main phases were implemented: (1) Training and Levelling, which equipped student volunteers with technical knowledge and soft skills, and (2) CoreTax Assistance, during which real-time SPT filing support was provided. Results demonstrate that structured, university-led tax assistance programs significantly enhance taxpayer compliance awareness and digital tax literacy. The collaboration between higher education institutions and tax authorities reflects best practices in tax education outreach and strengthens the sustainability of tax volunteer communities.